Hak Narapidana Tindak Pidana Narkotika untuk Memperoleh Pembebasan Bersyarat - Harun Sulianto (Fakultas Hukum Universitas Islam Jember, 2018)
In the criminal law enforcement process there is a provision concerning criminal sanctions in which the imposition of criminal sanctions for convicted offenders has a purpose. The purpose of giving criminal sanctions should be to foster not only serve as retaliation. Correctional institutions as implementers of the objective of punishment in the penal system as referred to in the Act, is a series of law enforcement that aims to ensure that the prisoners are aware of their mistakes, to improve themselves, and not to repeat the criminal acts so that they can be re-accepted by the community, actively participate in the development , And can live fairly as a good and responsible citizen.In an effort to re-populate the perpetrators of crime, Penal Institution through Act Number 12 of 1995 on Correctional regulation provides for the right of prisoners. In Article 14 paragraph (1) point k of Law Number 12 of 1995 states that